EFFECTIVE DEPTH OF VACUUM PRELOADING - J. Chu; S. W. Yan (Lowland Technology International, 2006)
Vacuum preloading is one of the methods that can be used to improve the engineering properties of soft clay. However, there is a misconception that the vacuum preloading method is only effective for soil within a depth of 10 m, as the maximum depth for water lifting using vacuum is 10 m. In this paper, the mechanisms of water lifting and vacuum preloading are examined and the differences between the two processes are explained. A simple physical model is used to demonstrate that the effective depth of vacuum preloading is not related to the maximum depth for water lifting. Two case studies are also presented to illustrate that in practice the vacuum preloading method can be used effectively for soil as deep as 20 m.